Green biosynthesis and characterization of magnetic iron oxide (Fe3O4) nanoparticles using seaweed (Sargassum muticum) aqueous extract - Mahdavi, Mahnaz; Namvar, Farideh; Ahmad @ Ayob, Mansor; Mohamad, Rosfarizan (MDPI, 2013)
The synthesis of nanoparticles has become a matter of great interest in recent times due to their various advantageous properties and applications in a variety of fields. The exploitation of different plant materials for the biosynthesis of nanoparticles is considered a green technology because it does not involve any harmful chemicals. In this study, iron oxide nanoparticles (Fe3O4-NPs) were synthesized using a rapid, single step and completely green biosynthetic method by reduction of ferric chloride solution with brown seaweed (BS, Sargassum muticum) water extract containing sulphated polysaccharides as a main factor which acts as reducing agent and efficient stabilizer. The structural and properties of the Fe3O4-NPs were investigated by X-ray diffraction, Fourier transform infrared spectroscopy, field emission scanning electron microscopy (FESEM), energy dispersive X-ray fluorescence spectrometry (EDXRF), vibrating sample magnetometry (VSM) and transmission electron microscopy. The average particle diameter as determined by TEM was found to be 18 ± 4 nm. X-ray diffraction showed that the nanoparticles are crystalline in nature, with a cubic shape. The nanoparticles synthesized through this biosynthesis method can potentially useful in various applications.